The Nexus Between ESG and Disaster Risk Resilience: Strengthening Financial Stability and Sustainable Development - Axel Giovanni; Jihad Lukis Panjawa; Kartika Pradana Suryatimur; Ika Amalia Nurunnisa; Siti Lailatul Khusna (LPPM Institut Bisnis dan Informatika Kesatuan, 2025)
Natural disasters pose significant economic and social challenges, particularly in vulnerable regions, necessitating strategies to enhance resilience. This study explores the relationship between Environmental, Social, and Governance practices and disaster risk resilience in financial institutions. The objective is to understand how these practices strengthen financial stability and sustainable development in high-risk environments. A systematic literature review was conducted using the Preferred Reporting Items for Systematic Reviews and Meta-Analyses extension for Scoping Reviews model, analyzing relevant articles from the Scopus database. Findings reveal that integrating Environmental, Social, and Governance practices enables financial institutions to conduct comprehensive risk assessments, leading to informed lending and investment decisions. These practices enhance resilience by mitigating financial shocks from disasters, fostering stakeholder relationships, and promoting sustainable investments. The study concludes that adopting Environmental, Social, and Governance principles significantly bolsters financial institutions' capacity to manage disaster risks, ensuring long-term stability and supporting sustainable development. However, challenges such as regional regulatory differences and data limitations highlight the need for further research to optimize these practices globally. This underscores the critical role of Environmental, Social, and Governance frameworks in building resilient financial systems.